The Efficacy of Art Therapy on Mental Health Outcomes Among Breast Cancer Patients: The Current State of Evidence Based on Randomised Controlled Trials - MN, Azmawati; B, Boekhtiar; M, Zawiah; M, Siti Aisah; WL, Chiew; R, Dalila (IIUM Medical Journal Malaysia, 2020)
Introduction: Breast cancer is the most common cancer among women. Psychosocial distress, in the forms of depression and anxiety, regularly accompanies breast cancer diagnosis and throughout its treatment. Hence, it is important to objectively assess the therapy options that may help this distress. One of the most flexible psychotherapy modalities is the art therapy as it may be incorporated in many settings. The purpose of this systematic review is to determine the efficacy of art therapy (via creative paintings) on the mental health outcomes of female breast cancer patients. Material and Methods: Related articles were identified from Medline (OvidSP), ScienceDirect, Pubmed, EbscoHost-Academic Search Premier and Wiley Online Library. Screenings were performed based on the criteria that the study must be a randomised control trial (RCT) that investigated the effect of art therapy in breast cancer. Data were extracted using standardised forms, followed by evaluation of quality of reporting using CONSORT Guidelines. Results: Six RCTs were identified. Based on the heuristic synthesis of data extraction results, none of the studies can be considered as studies with acceptable quality, although four of them showed promising results. Conclusion: There is inconclusive evidence of the efficacy of art therapy (via creative paintings) for the improvement of mental health outcomes among female breast cancer patients.